Navigating media literacy in the AI era: Analyzing gaps in two classic media literacy books (Journal of Applied Learning and Teaching, 2024)
The migration of the public into online platforms, the full mediatization of everyday life, the transformation of individuals into media entities via social media, the emergence of new forms of bottom-up censorship, and the involvement of non-human actors (such as AI) as media communicators and producers, have profoundly reshaped contemporary society. For these reasons, this study aims to analyze these pivotal transformations and assess how effectively they are addressed by two seminal media literacy texts, which have dominated the 21st century with media literacy editions, one by author James Potter and the other by Stanley Baran. Utilizing a problematization methodology, the research identifies gaps in these texts’ coverage of contemporary media phenomena and concepts. These two classic texts lack concepts that are very influential in today’s online life, such as mob censorship, social media literacy, post-truth and the role of AI in online communications. Moreover, integrating artificial intelligence into media production necessitates a practical approach to media literacy. This paper advocates for a holistic approach to media literacy education that equips learners with the skills needed to navigate and critically engage with today’s media landscape effectively.